Menggali Passion Membangun Karir: Pengabdian Masyarakat untuk siswa SMK - Nuristya, Emma Rani (Jurnal Pengabdian dan Pemberdayaan Masyarakat Kepulauan Riau (JPPM Kepri), 2025)
This community service aims to help Vocational High School (SMK) students understand the importance of passion in choosing the right career. With the theme "Exploring Passion, Building Careers," this activity seeks to provide students with insights into the connection between personal interests and career success. The program was carried out through seminars and counseling. The seminar featured speakers from various professions who shared their experiences and provided tips on developing a career based on passion. Meanwhile, counseling was conducted through individual and group sessions to offer deeper guidance on how to explore interests and plan careers. The results of the activity showed that 85% of students experienced an increased understanding of the relationship between passion and career, with many students starting to plan concrete steps to pursue careers in line with their interests. This activity also inspired students to feel more confident in choosing a career path that aligns with their talents and passions. It is hoped that this community service will make a positive contribution to preparing SMK students to face the workforce with greater readiness and motivation.